(untitled) (SCIENCE TIME JOURNAL, 2026)
The article analyzes gamification in foreign language teaching from the perspective of E. Deci and R. Ryan’s self-determination theory. The influence of game mechanics on the development of learners’ intrinsic motivation through the satisfaction of the basic psychological needs for autonomy, competence, and relatedness is examined. It is shown that the effectiveness of gamified learning depends on the balance between intrinsic and extrinsic motivation: the dominance of external incentives may lead to the overjustification effect and reduce learning activity. Based on the analysis of theoretical and applied studies, the paper formulates criteria for the methodologically justified use of game elements in foreign language teaching with regard to learners’ motivational levels.